Apart From Rhoptries, Identification of Toxoplasma gondii's O-GlcNAcylated Proteins Reinforces the Universality of the O-GlcNAcome - Aquino-Gil, Moyira Osny; Kupferschmid, Mattis; Shams-Eldin, Hosam; Schmidt, Jörg; Yamakawa, Nao; Mortuaire, Marlène; Krzewinski, Frédéric; Hardivillé, Stéphan; Zenteno, Edgar; Rolando, Christian; Bray, Fabrice; Pérez Campos, Eduardo; et al. (Frontiers in Endocrinology, 2018)
O-linked -N-acetylglucosaminylation or O-GlcNAcylation is a widespread post-translational modification that belongs to the large and heterogeneous group of glycosylations. The functions managed by O-GlcNAcylation are diverse and include regulation of transcription, replication, protein’s fate, trafficking, and signaling. More and more evidences tend to show that deregulations in the homeostasis of O-GlcNAcylation are involved in the etiology of metabolic diseases, cancers and neuropathologies. O-GlcNAc transferase or OGT is the enzyme that transfers the N-acetylglucosamine residue onto target proteins confined within the cytosolic and nuclear compartments. A form of OGT was predicted for Toxoplasma and recently we were the first to show evidence of O-GlcNAcylation in the apicomplexans Toxoplasma gondii and Plasmodium falciparum. Numerous studies have explored the O-GlcNAcome in a wide variety of biological models but very few focus on protists. In the present work, we used enrichment on sWGA-beads and immunopurification to identify putative O-GlcNAcylated proteins in Toxoplasma gondii. Many of the proteins found to be O-GlcNAcylated were originally described in higher eukaryotes and participate in cell shape organization, response to stress, protein synthesis and metabolism. In a more original way, our proteomic analyses, confirmed by sWGA-enrichment and click-chemistry, revealed that rhoptries, proteins necessary for invasion, are glycosylated. Together, these data show that regardless of proteins strictly specific to organisms, O-GlcNAcylated proteins are rather similar among living beings.